2004
DOI: 10.1007/s00415-004-0410-7
|View full text |Cite
|
Sign up to set email alerts
|

Vision and vertigo

Abstract: This review deals with two syndromes, oscillopsia and visual vertigo. Oscillopsia is the illusion of oscillation of the visual surroundings. For diagnosis purposes one should ask, when does the oscillopsia occur? If oscillopsia is only present during head (or whole body) movements, the likely underlying cause is a bilateral defect in the vestibulo-ocular reflex (VOR). The more common causes are post meningitic vestibular damage, gentamicin ototoxicity or bilateral idiopathic vestibular failure. When oscillopsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
39
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 148 publications
(43 citation statements)
references
References 42 publications
2
39
0
1
Order By: Relevance
“…In others, no history of a vestibular event can be obtained, but abnormalities are found on vestibular testing. It has been suggested that these subjects develop a compensation strategy for their vestibulo‐proprioceptive deficit and rely excessively on the visual input rendered thus “visually dependent” (Bronstein 2004, 2005). Lastly, in a proportion of VV patients, no vestibular lesion can be detected and their symptoms have been often considered to be of psychological origin (Schniepp et al.…”
Section: Introductionmentioning
confidence: 99%
“…In others, no history of a vestibular event can be obtained, but abnormalities are found on vestibular testing. It has been suggested that these subjects develop a compensation strategy for their vestibulo‐proprioceptive deficit and rely excessively on the visual input rendered thus “visually dependent” (Bronstein 2004, 2005). Lastly, in a proportion of VV patients, no vestibular lesion can be detected and their symptoms have been often considered to be of psychological origin (Schniepp et al.…”
Section: Introductionmentioning
confidence: 99%
“…[3, 4, 9] These symptoms have been defined as “visual vertigo”,[4, 27] and “space and motion discomfort”. [6, 10-12] Supermarkets, crowds, or even fence posts viewed within a person's peripheral vision can cause significant distress (increased dizziness, nausea, or even disorientation) in persons with complaints of visual vertigo.…”
Section: Introductionmentioning
confidence: 99%
“…[6, 10-12] Supermarkets, crowds, or even fence posts viewed within a person's peripheral vision can cause significant distress (increased dizziness, nausea, or even disorientation) in persons with complaints of visual vertigo. [4, 5, 19] Symptoms of visual vertigo have also been reported in persons without vestibular dysfunction. [9, 16]…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations